Changing Trends in Meteorological Elements and Reference Evapotranspiration in a Mega City: A Case Study in Shenzhen City, China. (18th May 2015) - Liu, Haijun; Zhang, Xian; Zhang, Liwei; Wang, Xuming
Abstract : Shenzhen city was a farmland region before 1978, and it then developed to a mega city in China. This type of change in city can greatly affect the climatic conditions. In this study, the daily, monthly, and annual climatic variables and the reference crop evapotranspiration (ET0 ) for Shenzhen from 1954 to 2012 were computed using the FAO Penman-Monteith equation (PM), and these parameters were analyzed to study the temporal trends of ET0 and meteorological factors. The trends and the time points of abrupt changes of ET0 and meteorological factors were tested using Mann-Kendall methods. Results show that, in the past 59 years, the annual ET0 first decreased from 1954 to 1978, then increased from 1979 to 1990, and now varied slightly after 1990. The mean air temperature rose gradually, and the relative humidity decreased as a whole. These trends finally resulted in an increasing trend in vapor pressure deficit (VPD). The wind speed showed a slightly decreasing trend. Both the annual total sunshine duration and net radiation showed trends of rapid decline. ET0 change is sensitive to the hours of sunshine and VPD. The significant increase in ET0 after 1979 was mainly due to the increased air temperature and decreased relative humidity.